FAKTOR YANG BERPENGARUH TERHADAP KECEPATAN TERJADINYA KATARAK SENILIS DI RS. KHUSUS MATA PROVINSI SUMATERA SELATAN - Kesuma, Imaniar; Triwibowo, Anang; Bahar, Erial (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Cataracts are any condition of opacity in the lens that can occur due to the hydration (fluid addition) of the lens, the lens protein denaturation or the consequences of both. Based on the World Health Organization (WHO) data, cataracts can cause blindness in more than 17 million people in the world. Factors that can affect the development rate of opacity of the lens such as diabetes mellitus, hypertension, certain medications, the B ultra violet rays from sunlight, toxic effects of smoking, alcohol, less vitamin E, and chronic inflammation in the eyeball. The type of research used is observational analytical research with cross sectional design. This study was held in August to December in 2019 in RS. Special Eye of South Sumatera province with sampling as many as 234 patients from medical record. Data is processed using SPSS. The Chi-square test is conducted to determine the relationship of factors that affect the rate of senile cataract in RS. Khusus Mata Provinsi Sumatera Selatan. From 234 patients, as many as 177 patients (75.6%) with mature cataract and 57 patients (24.4%) with immature cataract. There is no meaningful relation between senile cataract and hypertension (p = 0,068; OR = 1,084; 95% CI = 0,589-1,995). There is no meaningful relation between senile cataract and diabetes mellitus (p = 1.808; OR = 1,876; 95% CI = 0,741-4,747). There is no meaningful relation between senile cataract and gender (p = 0.51; OR = 0,933; 95% CI = 0,514-1,696). There is no meaningful relation between the senile cataract and age (p = 0,784; OR = 1,319; 95% CI; 0,714-2,437). There is no meaningful relation between senile cataract and hypertension. There is no meaningful relation between senile cataract and diabetes mellitus. There is no meaningful relation between senile cataract and gender. There is no meaningful relation between the senile cataract and age.